115PDetection of actionable variants in various cancer types reveals value of whole-genome sequencing over in-silico whole-exome and hotspot panel sequencing. (7th November 2019) - Ramarao-Milne, K P; Patch, A-M; Nones, K; Koufariotis, R; Newell, F; Addala, V R; Kondrashova, O; Mukhopadhyay, P; Kazakoff, S H; Lakis, V; Holmes, O; Leonard, C; et al.
Abstract: Background: Declining costs of next-generation sequencing technologies has led to their more widespread use for the identification of targetable mutations. Nonetheless, while multigene panels are being assimilated into clinical practice, the use of whole-exome and whole-genome sequencing (WES and WGS) remains limited, as its added value is unclear in the clinic. Methods: In our study, we have used the Cancer Genome Interpreter (CGI) to identify the actionable variants that are detected by WGS and compared this to in-silico down-sampled regions of WES and a hotspot panel. Results: We show that within some tumour types, WGS is invaluable in identifying actionable variants that involve copy number defects and structural aberrations. Moreover, WGS successfully identifies many resistance biomarkers that would have otherwise been missed by WES and panels, particularly in the breast cancer dataset studied. WGS is more valuable of the detection of actionable variants in some tumour types, whereas hotspot panels perform well for other tumour types. Additionally, we show that a tumour type-agnostic approach to selecting genomic biomarker-based drug allocation increases the number of possible FDA-approved and clinical trial-based drug prescriptions for any given genomic biomarker in the patient cohorts studied. Conclusions: Taken together, we show that WGS has the potential to impact patient care by identifying more targetable mutations and therefore expand drug options available for the patient. Furthermore, we illustrate the potential of tumour type-agnostic drug repurposing in nine cancer datasets. Legal entity responsible for the study: QIMR Berghofer Medical Research Institute. Funding: QIMR Berghofer Medical Research Institute. Disclosure: All authors have declared no conflicts of interest.